The Effect of Capital Structure, Liquidity, and Firm Size on Firm Value in The Technology Industry Sector Listed on the IDX - Anita, Anita; Suhardi, Suhardi; Makrus, Mohamad; Radiansyah, Adrian (Lembaga Riset Mutiara Akbar (LARISMA), 2025)
This study examines the influence of capital structure, liquidity, and firm size on firm value in the technology sector listed on the Indonesia Stock Exchange for 2019–2023. Using panel data regression with the random effects model, the results reveal that both capital structures, as measured by Debt-to-Equity Ratio, and liquidity, as measured by Current Ratio, have a significant and positive effect on firm value. The findings indicate that technology companies that manage their leverage and liquidity efficiently tend to achieve higher market valuations. In contrast, firm size does not have a significant impact on firm value in this sector. The results are consistent with the Trade-Off Theory and Liquidity Theory, which emphasize the importance of optimal debt usage and adequate liquidity for enhancing firm value and investor confidence. These findings have practical implications for technology firms to optimize their capital structure and maintain healthy liquidity levels. For future research, it is recommended to include other variables such as profitability and macroeconomic factors, and to conduct comparative studies across different sectors to enrich the understanding of determinants of firm value.